1999
DOI: 10.1074/jbc.274.48.33863
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Purification of Hydroxyisourate Hydrolase, a Novel Ureide-metabolizing Enzyme

Abstract: We report the identification and purification of a novel enzyme from soybean root nodules that catalyzes the hydrolysis of 5-hydroxyisourate, which is the true product of the urate oxidase reaction. The product of this reaction is 2-oxo-4-hydroxy-4-carboxy-5-ureidoimidazoline, and the new enzyme is designated 5-hydroxyisourate hydrolase. The enzyme was purified from crude extracts of soybean root nodules ϳ100-fold to apparent homogeneity with a final specific activity of 10 mol/ min/mg. The enzyme exhibited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 10 publications
2
40
0
Order By: Relevance
“…The third enzyme, OHCU decarboxylase, was identified through the phylogenetic analysis of a whole genome and has been shown to catalyze the decarboxylation of OHCU, producing the stereospecific (S)-allantoin (8). These observations are consistent with the previous identification of two chemically distinct labile intermediates produced by urate oxidase (9) but differ in that racemic allantoin is produced in the nonenzymatic decomposition of HIU (10).…”
supporting
confidence: 81%
“…The third enzyme, OHCU decarboxylase, was identified through the phylogenetic analysis of a whole genome and has been shown to catalyze the decarboxylation of OHCU, producing the stereospecific (S)-allantoin (8). These observations are consistent with the previous identification of two chemically distinct labile intermediates produced by urate oxidase (9) but differ in that racemic allantoin is produced in the nonenzymatic decomposition of HIU (10).…”
supporting
confidence: 81%
“…Tipton and colleagues have provided details of the urate oxidase-catalyzed reaction (5,6) and subsequently identified a gene for HIUHase from soybean (G. max) (7,8). The 560-aa soybean HIUHase does not share any sequence similarity with PucM, but belongs to family 1 of glycosidase (9).…”
Section: Discussionmentioning
confidence: 99%
“…1.7.3.3; uricase), but recent investigations have revealed that this pathway includes two additional, distinct, chemically labile intermediates: 5-hydroxyisourate (HIU) and 2-oxo-4-hydroxy-4-carboxy-5-ureidoimidazoline (OHCU) (5,6). It is now generally believed that urate oxidase is responsible only for the conversion of uric acid into HIU, and a second enzyme, HIU hydrolase (HIUHase), catalyzes the hydrolysis of HIU into OHCU (7)(8)(9)(10)(11), which is then converted into allantoin via an enzyme-dependent decarboxylation reaction (Scheme 1) (11). Recently, three genes were characterized as HIUHases: a soybean (Glycine max) gene (7,8), PucM in Bacillus subtilis (10), and MuraH in mice (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1), where ureides provide the major transport form of symbiotically fixed dinitrogen (29,43,48,55). Until recently, it was thought that allantoin was formed directly from uric acid by the action of uric acid oxidase (39); however, it has now been established that the true product of soybean uric acid oxidase is 5-hydroxyisourate (22), which is then acted upon by the enzyme hydroxyisourate hydrolase to yield 2-oxo-4-hydroxy-4-carboxy-5-ureidoimidazoline (42). This compound is then converted to allantoin, most likely by a yet unidentified enzyme.…”
mentioning
confidence: 99%